Agriculture of microalgae Chlorella vulgaris for polyunsaturated fatty acids (PUFAs) production employing palm oil mill eﬄuents (POME) for future food, wastewater, and energy nexus - Kumaran, Monaambighai; Palanisamy, Karthick Murugan; Bhuyar, Prakash; Maniam, Gaanty Pragas; Mohd Hasbi, Ab. Rahim; Govindan, Natanamurugaraj (Elsevier Ltd, 2023)
Malaysia is one of the second largest world palm oil exporters; correspondingly, the massive production of palm oil mill effluent (POME) is a significant concern. The present investigation aimed to isolate and characterize the potential microalgae and maximize the growth and biomass productivity of Chlorella sp. using POME. Chlorella vulgaris was cultured in BG-11 (control) and POME with 1:1, 1:2, 1:3, and 1:4 dilution ratios. Binary solvent extraction was applied to extract lipids, and polyunsaturated fatty acids (PUFAs) in the fatty acid methyl ethers were determined using gas chromatography coupled with mass spectrometry (GC-MS). Results suggest the lipid level of 21 wt.% was the highest amount obtained from biomass Chlorella vulgaris cultivated in 1:4 diluted POME. Chlorella sp. in POME with a 1:4 dilution ratio gives the highest biomass yield. It also yields the maximum dry cell weight of 0.42 g/L. Therefore, this study indicates that diluted POME with different dilutions is a suitable growth medium for Chlorella vulgaris biomass cultivation. Pairing wastewater with algae culture reduces biomass production and water treatment costs. Further studies demand more attention for future food, wastewater, and energy nexus.